Ultrasound, Gender, and Consent: An Apparent Feminist Analysis of Medical Imaging Rhetorics. Issue 1 (2nd January 2021) - Frost, Erin A.
ABSTRACT: This article uses an apparent feminist approach to engage a two-part research question: First, does gender affect the frequency with which people become subjects of medical digital imaging? Second, how do the subjects of medical digital imaging become persuaded to accept this role? Engaging with medical imaging and the technical communication surrounding it as an assemblage of technical rhetorics (Frost & Eble) and thus a technology, this project shows that women are more commonly scanned as a result of social biases. Further, this article argues that the ubiquity of scanning of women's bodies has implications for political agency and privacy and for technical communicators' understandings of efficiency. This study is preliminary but presents compelling evidence that further research on the technical communication surrounding gender and medical imaging is necessary.